Mathematical modeling of trypanosomiasis control strategies in communities where human, cattle and wildlife interact - Mlyashimbi Helikumi; Steady Mushayabasa (BMC, 2023)
Abstract Spillover of trypanosomiasis parasites from wildlife to domestic livestock and humans remains a major challenge world over. With the disease targeted for elimination by 2030, assessing the impact of control strategies in communities where there are human-cattle-wildlife interactions is therefore essential. A compartmental framework incorporating tsetse flies, humans, cattle, wildlife and various disease control strategies is developed and analyzed. The reproduction is derived and its sensitivity to different model parameters is investigated. Meanwhile, the optimal control theory is used to identify a combination of control strategies capable of minimizing the infected human and cattle population over time at minimal costs of implementation. The results indicates that tsetse fly mortality rate is strongly and negatively correlated to the reproduction number. It is also established that tsetse fly feeding rate in strongly and positively correlated to the reproduction number. Simulation results indicates that time dependent control strategies can significantly reduce the infections. Overall, the study shows that screening and treatment of humans may not lead to disease elimination. Combining this strategy with other strategies such as screening and treatment of cattle and vector control strategies will result in maximum reduction of tsetse fly population and disease elimination.